Study of polypropylene surface modification by air dielectric barrier discharge operated at two different frequencies - Kostov, K. G.; Nishime, T. M C; Hein, L. R O; Toth, A. (Elsevier, 2012)
In this work, air dielectric barrier discharge (DBD) operating at the line frequency (60 Hz) or at frequency of 17 kHz was used to improve the wetting properties of polypropylene (PP). The changes in the surface hydrophilicity were investigated by contact angle measurements. The plasma-induced chemical modifications of PP surface were studied by X-ray photoelectron spectroscopy (XPS) and Fourier-transformed infrared spectroscopy (FTIR). The polymer surface morphology and roughness before and after the DBD treatment were analyzed by atomic force microscopy (AFM). To compare the plasma treatment effect at different frequencies the variation of the contact angle is presented as a function of the deposited energy density. The results show that both DBD treatments leaded to formation of water-soluble low molecular weight oxidized material (LMWOM), which agglomerated into small mounts on the surface producing a complex globular structure. However, the 60 Hz DBD process produced higher amount of LMWOM on the PP surface comparing to the 17 kHz plasma treatment with the same energy dose. The hydrophilic LMWOM is weakly bounded to the surface and can be easily removed by polar solvents. After washing the DBD-treated samples in de-ionized water their surface roughness and oxygen content were reduced and the PP partially recovered its original wetting characteristics. This suggested that oxidation also occurred at deeper and more permanent levels of the PP samples. Comparing both DBD processes the 17 kHz treatment was found to be more efficient in introducing oxygen moieties on the surface and also in improving the PP wetting properties. © 2012 Elsevier B.V. All rights reserved.
Keywords: Dielectric barrier discharge; Oxidation; Plasma surface modification; Polypropylene; Surface morphology